Analysis of The Effectiveness of Information Management and Innovation Behavior on Hospitals Organizational Performance in Indonesia - Ekasari, Silvia; Abdurakhman, R Nur; Uli Wildan Nuryanto; Hartanto; Wulandari (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to analyze the feasibility of technology adoption to improve hospital business performance in Indonesia. The study uses an applied descriptive method. The unit of analysis in this study is the surgical department in both private and public hospitals. Data were collected from internal records and questionnaires. The sampling technique was non-probabilistic. The results of the study analysis indicate that hospital management is currently facing obstacles and challenges related to record management, on the other hand, management realizes that they also find and identify that there are great opportunities to improve and enhance business performance through the use of technology and implementation of management systems in business processes. Detailed and easily accessible record management is essential to ensure patient safety and build effective management capacity. Automation and integrated systems are needed to increase focus on patient satisfaction levels, because high administrative burdens often distract from clinical aspects. The suggestion from the study is that management needs to update the computerization system so that the digitalization process of business processes can run well. Another suggestion is that management needs to improve the quality of human resources and make investments related to the adoption of the latest technology is very important to improve work efficiency and effectiveness